2004
DOI: 10.1002/hep.20465
|View full text |Cite
|
Sign up to set email alerts
|

Initial response to percutaneous ablation predicts survival in patients with hepatocellular carcinoma

Abstract: Outcome predictors in patients with hepatocellular carcinoma (HCC) who are treated with percutaneous ablation are ill defined, and it is unknown if successful therapy is associated with improved survival. In our study, 282 cirrhotic patients with early nonsurgical HCC were treated with percutaneous ablation during a 15-year period. Single tumors were seen in 244 patients, and 2 to 3 nodules were seen in 38 patients. Initial complete response was achieved in 192 patients and was independently related to the siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

36
282
2
10

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 419 publications
(333 citation statements)
references
References 36 publications
36
282
2
10
Order By: Relevance
“…Although this may have increased the number of treatment sessions, complete ablation is possibly associated with improved prognosis. 36 While there was no difference in early complication rates according to tumor location, the overall early complication rate of 4.2% in this study may be slightly higher than those reported in other studies. 21,37 The effort of thorough ablation increased the total number of electrode insertions, and this may have led to an increase in complications.…”
Section: Discussioncontrasting
confidence: 76%
“…Although this may have increased the number of treatment sessions, complete ablation is possibly associated with improved prognosis. 36 While there was no difference in early complication rates according to tumor location, the overall early complication rate of 4.2% in this study may be slightly higher than those reported in other studies. 21,37 The effort of thorough ablation increased the total number of electrode insertions, and this may have led to an increase in complications.…”
Section: Discussioncontrasting
confidence: 76%
“…This therapeutic option is more commonly used in oriental countries. PEI achieves complete tumor necrosis in 90% of tumors < 2 cm, 70% in those of 2 cm -3 cm and 50% in those between 3 cm and 5 cm [44,61,62] . The fact that its action may be blocked either by the intra-tumoral fibrotic septa or the tumor capsule, undermines the curative capacity of this technique, particularly in tumors larger than 2 cm [1] .…”
Section: Percutaneous Ethanol Injectionmentioning
confidence: 95%
“…Similarly, although some tumoral markers (mainly AFP), have shown an indisputable prognostic power (60)(61)(62)(63)(64), there is no consensus in terms of determining a pathological cutoff value, and these markers do not have enough strength to evaluate patients in an individual way and in most clinical scenarios, they do not induce a change in therapeutic approach (7). Therefore, one of the current challenges in clinical research is to try to integrate gene expression data in the current evaluation systems and basing the survival prediction and treatment indication in the molecular profile of the patient.…”
Section: Refining Prognostic Assessment and Therapeutic Decisionmentioning
confidence: 99%